HUBUNGAN LINGKUNGAN KERJA DAN UPAH TERHADAP MOTIVASI KERJA PADA KARYAWAN GERAI KULINER DI METROPOLITAN CITY (MTC) PANAM - Rona Meliza; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at MTC Panam, Pekanbaru city. The purpose of this research is to find out: 1) How is the work environment and wages received by culinary outlet employees at MTC Panam 2) How is the work motivation of culinary outlet employees at MTC Panam 3) How is the influence of the work environment and wages on the work motivation of culinary outlet employees at MTC Panam MTC Panam. This research uses an inferential quantitative method. the population of this study were employees of culinary outlets at MTC Panam totaling 70 people and the sample in this study was 41 respondents. Sampling using simple random sampling technique (simple random sampling). the data instruments are Observation, Interview and Documentation. Based on the results of the study, it can be concluded that the work environment based on indicator data of lighting, air temperature, noise, use of color, space, work security and employee relations at culinary outlet employees at MTC Panam is quite comfortable with a frequency of 34 respondents. The wages received by employees of culinary outlets at MTC Panam are seen from the data on indicators of wages and salaries, incentives and bonuses, THR and facilities received by employees, the wages received by employees of culinary outlets at MTC Panam are in accordance with the frequency of 29 respondents who feel they are in accordance with their needs. The work motivation of culinary outlet employees at MTC Panam is high with a frequency of 40 respondents. There is a relationship between work environment and wages with work motivation. There is an influence of the work environment and wages on employee work motivation, the better the work environment and wages, the higher the work motivation. Keywords: Relationship, Work Environment, Wages, Work Motivation